2018
DOI: 10.1016/j.foodchem.2017.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Novel hydroxypyridinone derivatives containing an oxime ether moiety: Synthesis, inhibition on mushroom tyrosinase and application in anti-browning of fresh-cut apples

Abstract: A range of hydroxypyridinone derivatives were synthesized starting from kojic acid. Among them, 10 and 11 were found to possess the strongest inhibitory effect on monophenolase activity of mushroom tyrosinase, having IC values of 2.04 and 1.60μM, respectively. The IC values of 10 and 11 for the inhibition of diphenolase activity of mushroom tyrosinase were determined as 13.89 and 7.99μM, respectively. Investigation of the inhibitory mechanism of these two compounds indicated that the inhibition was reversible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 39 publications
2
34
1
Order By: Relevance
“…Tyrosinase catalyses the oxidation of phenolic compounds to the corresponding quinones and is responsible for the enzymatic browning of fruits and vegetables, which display a characteristic undesirable colour and flavour. The oxidation products of phenolic compounds can then react with other food components, including amines, peptides, and proteins, which further reduces food quality and digestibility (Shao et al, 2018). Tyrosinase also plays a critical role in the biosynthesis of melanin and its over-activity can cause skin hyperpigmentation (Niu and Aisa, 2017).…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…Tyrosinase catalyses the oxidation of phenolic compounds to the corresponding quinones and is responsible for the enzymatic browning of fruits and vegetables, which display a characteristic undesirable colour and flavour. The oxidation products of phenolic compounds can then react with other food components, including amines, peptides, and proteins, which further reduces food quality and digestibility (Shao et al, 2018). Tyrosinase also plays a critical role in the biosynthesis of melanin and its over-activity can cause skin hyperpigmentation (Niu and Aisa, 2017).…”
Section: Anti-tyrosinase Activitymentioning
confidence: 99%
“…Monophenolase and diphenolase activity was measured as described previously by monitoring the dopachrome absorbance at 475 nm 17 . L-Tyrosine and L-DOPA were used as reaction substrate for monophenolase and diphenolase assays, respectively.…”
Section: Monophenolase and Diphenolase Inhibition Assaymentioning
confidence: 99%
“…Molecular docking was performed by using CDOCKER module embedded in Discovery Studio 2.5 software (Accelrys Software, Inc., San Diego, CA, USA) 17 . The X-ray crystal structure of tyrosinase from Agaricus bisporus (PDB ID: 2Y9X) was retrieved from the Protein Data Bank (http://www.rcsb.org/pdb).…”
Section: Molecular Docking Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been demonstrated that some hydroxypyridinone derivatives effectively retard the browning of shrimp (Dai et al, 2016). Recently, a range of hydroxypyridinone derivatives containing an oxime ether moiety have been synthesized starting from kojic acid in our laboratory (Shao et al, 2018). Among them, 5-hydroxy-1-octyl-4-oxo-1,4-dihydropyridine-2-carbaldehyde O-ethyl oxime (1, Fig.…”
Section: Introductionmentioning
confidence: 99%